The Importance of Habitat and Microclimate on the Functional and Guild Structure of Canopy-Dwelling Beetle Communities in Subantarctic Forest - Vergara-Egert, P; Fierro-Tapia, C; Alaniz-Baeza, A; Carvajal-Leon, M (Springer Science and Business Media B.V., 2024)
Beetle species living in high-latitude forests may be sensitive to variations in habitat conditions and microclimate. We tested that the functional traits and guild structure of canopy-dwelling beetle species of the southernmost subantarctic forests respond to habitat and microclimate. Beetles were collected in 50,400 m radius circular landscapes regularly distributed over the study area, where habitat and microclimate variables were quantified. We assigned species to representative ecological guilds and estimated four components of functional diversity using traits related to feeding ecology, dispersion, size and color patterns. Generalized linear mixed models were used to estimate the additive and interactive effects of habitat and microclimate. The cover of open habitats (peatbogs and meadow) and landscape diversity had a negative effect on functional dispersion and richness, as well as on the abundance of large-sized, small-sized and saproxylic species. The moisture stress index (MSI) negatively affected the abundance of all species, large-sized species and saproxylic species. Winter temperature positively affected predators and interacted with woodpecker’s foraging holes to positively affect small-sized species. A larger density of dead trees positively influenced large-sized species and reduced the negative effect of elevation and MSI on saproxylic species. These findings suggest that human-created habitat heterogeneity engages in negative effects on different guilds of beetles whereas climate conditions are limiting factors. However, unfavorable microclimate conditions are buffered by habitat and microhabitat features. Therefore, the conservation of beetle assemblages in high-latitude forests requires the preservation of habitats and microhabitats providing less stressful climate conditions to beetles. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.